Faces/Phases and Other Poems - Carnice, F. Jordan (Likhaan: The Journal of Contemporary Philippine Literature, 2024)
Experiencing a pandemic in the Philippines is in itself a result of a deeper systematic ailment that has plagued this country for years, and in this current administration, the remedy to both illnesses is becoming more and more like a pipedream. This small suite of poems tries to versify this experience, particularly how most of our choices during this health crisis are burdened by the economic, political, social, and even environmental impacts caused by policies, laws, or guidelines reflect little understanding of people’s welfare. In short, many of us are (still) bound to suffer(ing), with or without COVID-19.